TA’WÎL TAFSIR PERIODE MODERN: Telaah Tafsir Al-Marâghî Karya Ahmad Musthâfâ - Hakim, Muhammad Naufal (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
This article is a study of the ta’wîl pattern in the book of Al-Tafsîr Al-Marâghî. Tafsîr Al-Marâghî is a book that appeared in the modern period and became the magnum opus Ahmad Musthâfâ Al-Marâghî. Using descriptive-analytical method, there are two main studies: 1.) The sources and methodes of interpretation of Ahmad Musthafâ Al-Marâghî; 2.) The pattern of ta’wîl in Al-Tasfîr Al-Marâghî and its relevance to the development of modern interpretation. This research resulted in Al-Tafsîr Al-Marâghî being a book whose interpretation comes from the Qur’ân, hadith, qaul shahabi, language, ulama, ijtihad, and 30 reference of previous books. Using two methods of interpretation at once, ijmâly and tahlîliy, this book is patterned by al-adab al-ijtim‘î, and has characteristics with using naql and ‘aql when interpreting of the Qur’an. Ta’wîl in Al-Tafsîr Al-Marâghî had two patterns, firstly in focusing on linguistic indicators, and the secondly focusing on ratios and is critical. The application of these two ta’wîl patterns can represent a modern period interpretation model that was born in a pragmatic and logical society.